Modulation of Antioxidant Defense System Is Associated with Combined Drought and Heat Stress Tolerance in Citrus - Zandalinas, Sara I.; Balfagón, Damián; Arbona, Vicent; Gómez-Cadenas, Aurelio (Frontiers in Plant Science, 2017)
Drought and high temperatures are two major abiotic stress factors that often occur simultaneously in nature, affecting negatively crop performance and yield. Moreover, these environmental challenges induce oxidative stress in plants through the production of reactive oxygen species (ROS). Carrizo citrange and Cleopatra mandarin are two citrus genotypes with contrasting ability to cope with the combination of drought and heat stress. In this work, a direct relationship between an increased antioxidant activity and stress tolerance is reported. According to our results, the ability of Carrizo plants to efficiently coordinate superoxide dismutase (SOD), ascorbate peroxidase (APX), catalase (CAT) and glutathione reductase (GR) activities involved in ROS detoxification along with the maintenance of a favorable GSH/GSSG ratio could be related to their relative tolerance to this stress combination. On the other hand, the increment of SOD activity and the inefficient GR activation along with the lack of CAT and APX activities in Cleopatra plants in response to the combination of drought and heat stress, could contribute to an increased oxidative stress and the higher sensibility of this citrus genotype to this stress combination.